2018
DOI: 10.2196/10434
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Literacy Across the Lifespan: Measurement Invariance Study

Abstract: BackgroundElectronic health (eHealth) information is ingrained in the healthcare experience to engage patients across the lifespan. Both eHealth accessibility and optimization are influenced by lifespan development, as older adults experience greater challenges accessing and using eHealth tools as compared to their younger counterparts. The eHealth Literacy Scale (eHEALS) is the most popular measure used to assess patient confidence locating, understanding, evaluating, and acting upon online health information… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(132 citation statements)
references
References 68 publications
(95 reference statements)
8
117
1
6
Order By: Relevance
“…12,22,28 This was also concluded in the initial work by Norman and Skinner. 16 On the other hand, several studies have also shown an inherent structure with two 12,19,23,24 or three 12,30 factors reflecting the underlying content of electronic health literacy, as previously described.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…12,22,28 This was also concluded in the initial work by Norman and Skinner. 16 On the other hand, several studies have also shown an inherent structure with two 12,19,23,24 or three 12,30 factors reflecting the underlying content of electronic health literacy, as previously described.…”
Section: Introductionmentioning
confidence: 55%
“…This tendency is also reported in other studies. 23,30 For instance, Paige et al 30 found that older adults experienced greater challenges regarding eHealth resource awareness, information seeking skills, and ability to evaluate and act upon online health information, compared with younger adults. However, the Internet use among older people is steadily increasing, as they search and visit websites for on-line health information and discussion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Physicians, and pharmacists are more trusted sources than online information, and it is a proven that older adults are less vulnerable to web-health. 27 On the other hand, preliminary results of online usage for pregnancy check in Netherlands women have found that 50% of them made their decisions through the internet. 28 Oncology patients are using the internet to get information about their disease and were happy to receive useful website links through their physicians.…”
Section: Survey 34mentioning
confidence: 99%